Analysis of trends in the development of load codes for building structures - Pichugin , Sergii (Academic journal Industrial Machine Building Civil Engineering, 2024)
The content of the article is a consistent review of approaches to considering loads on building structures and their reflection in regulatory documents of different years. Attention is focused on the continuity of the method of limit states and the method of permissible stresses in the part of the description of loads. With regard to climatic loads (snow, wind), attention is paid to changes in territorial zoning and calculation coefficients, the assignment of normative and calculation values and the involvement of experimental statistical data. Attention is also paid to the connection between the development of codes of crane loads and the results of experimental studies of these loads.